Intellectual Property in Asian Emerging Economies : Law and Policy in the Post-TRIPS Era. - Endeshaw, Assafa (Ashgate Pub., 2010)
This book critically reviews the recurrent debate on Intellectual Property law and policy in Developing Countries carried out in the last decade; to identify the still unresolved policy issues and to propose alternative approaches that resonate with the needs for transformation of the economic and social reality of DCs. It draws lessons to be learnt by researchers, policy makers, legislators and the business sector in general and concludes by putting forward proposals for reform.